Differences in health literacy domains among migrants and their descendants in Germany - Berens, Eva-Maria; Klinger, Julia; Carol, Sarah; Schaeffer, Doris (Frontiers in Public Health, 2022)
Background Health literacy (HL) is considered to be an important precondition for health. HL research often identifies migrants as vulnerable for low HL. However, in-depth data on HL among migrants especially in its domains of health care, disease prevention and health promotion and its determinants are still scarce. Objective The aim of this study was therefore to analyse the current status of HL among migrants and their descendants from Turkey and from the former Soviet Union (FSU) in Germany and factors associated with it. This has not been studied using large-scale data and bilingual interviews. We differentiate between dimensions of HL, namely the domains of health care, disease prevention and health promotion which goes beyond many previous studies. In addition, we explore new mechanisms by testing the explanatory power of self-efficacy and interethnic contacts for migrants' HL. Methods The study includes 825 first- and second-generation adult migrants from two of the largest immigration groups in Germany, from Turkey and FSU, who were interviewed face-to-face in German, Turkish or Russian in late summer 2020. HL was measured using the HLS19-Q47 instrument. Age, gender, educational level, social status and financial deprivation, chronic illness, health-related literacy skills, self-efficacy, interethnic contacts, migration generation, duration of stay and region of origin were considered as possible determinants. Ordinary least square regressions were estimated. Results The average general HL score was 65.5. HL in health promotion and disease prevention was lower than in health care. Low financial deprivation, health-related literacy skills, and self-efficacy were positively correlated with each HL domain. Educational level, social status, age, gender, duration of stay and interethnic contacts were positively correlated with HL in some domains. Region of origin was only correlated with the domain of disease prevention until interethnic contact was accounted for. Conclusion Our study contributes to the existing knowledge by analyzing different domains of HL and testing its correlations with self-efficacy and interethnic contact among migrants. We reveal that migrants cannot generally be considered as vulnerable for low HL, as oftentimes outlined. There is a need for interventions e.g. to enhance the understanding of health information among subgroups with lower HL.